Narrative and Affect in William Gillespie's Keyhole Factory and Morpheus: Biblionaut, or, Post-Digital Fiction for the Programming Era. Issue 2 (August 2016) - Rasmussen, Eric Dean
Abstract : Programmable computation is radically transforming the contemporary media ecology. What is literature's future in this emergent Programming Era? What happens to reading when the affective, performative power of executable code begins to provide the predominant model for creative language use? Critics have raised concerns about models of affective communication and the challenges a-semantic affects present to interpretive practices. In response, this essay explores links between electronic literature, affect theory, and materialist aesthetics in two works by experimental writer and publisher William Gillespie. Focusing on the post-digital novel Keyhole Factory and the electronic speculative fiction Morpheus: Bilblionaut, it proposes that: first, tracing tropes of code as affective transmissions allows for more robust readings of technomodernist texts and, second, examining non-linguistic affect and its articulation within constraint-based narrative forms suggests possibilities for developing an affective hermeneutics. My project was prompted by calls for more in-depth critical interpretations of works of electronic literature; an appreciation of how Gillespie problematises tropes of proximity and distance used to characterise modes of critical reading; and a desire to explain Gillespie's commitment to both conceptual, constraint-based writing practices (facilitated by computational media) and the intentional production of meaningful narrative affect. Ultimately, my analyses showcase Gillespie's countertextual achievement: assembling a network of texts, both electronic and analogue, that functions as a literary ecosystem resistant to the instrumentalism of the neoliberal publishing industry. Gillespie's Spineless Books provides an exemplary model of and working platform for collaborative, conceptual, and countertextual literary writing across media.